Detection of Epstein-Barr virus in different sources of materials from patients with oral lichen planus: a case-control study - Vieira, Rubia da Rocha; Ferreira, Ligia Lavezo; Biasoli, Eder Ricardo; Bernabe, Daniel Galera; Nunes, Caris Maroni; Miyahara, Glauco Issamu (Bmj Publishing Group, 2016)
Aims To detect the presence of Epstein-Barr virus (EBV) DNA in different sources of materials from a matched group of patients with oral lichen planus (OLP) and a group of people without OLP lesions, and to correlate the presence of virus with epidemiological variables of the groups studied. Methods Fresh tissue samples, saliva, exfoliated cells and plasma of 24 patients with OLP lesions (cases) and 17 patients without OLP lesions (controls) were collected. EBV was detected by nested PCR. Results Viral positivity was obtained in 62.5% of tissue samples; in 70.8% of exfoliated cell samples; in 33.3% of blood plasma samples and in 75% of saliva samples in the cases; and in 35.3% of tissue samples; 82.4% of exfoliated cell samples; in 47.1% of blood plasma samples and in 64.7% of saliva samples in the controls. There was a predominance of women in both groups. Variables not atrophic-erosive were most affected by EBV. Conclusions No relationship between EBV and OLP was found. However, all sources tested in this study were considered suitable for the detection of viruses.